ADOPTING A HEALTHY LIFESTYLE CAN PREVENT CANCER - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
It is estimated that almost a third of all cancer cases could have been prevented by adopting a healthy lifestyle and improving environmental conditions. For this reason, it is crucial to promote awareness and prevention, including various types of communicable diseases and chronic ailments to ensure the wellbeing of the public.